Being the change : a guide for advocates and activists on staying healthy, inspired, and driven - Friedman-Wheeler, Dara G.; Bodenlos, Jamie S. (APA LifeTools Ser., 2023)
"This book offers practical tips for readers who want to be effective advocates and agents of change, while coping with the emotional and relational challenges such work often presents"--